أثر الخصائص الإسنادية في ترتيب أحاديث الباب في صحيح الإمام مسلم -دراسة تطبيقية - حنانشة, مصطفى (University of eloued جامعة الوادي, 2016)
یقوم هذا البحث بد ا رسة أثر الخصائص الإسنادیة في ترتیب أحادیث الباب في صحیح الإمام مسلم، وقد انبنى من مقدمة وثلاثة فصول و خاتمة، حیث خصصت المقدمة للتعریف بالموضوع و أهمیته و أسباب اختیاره، ثم قمت في الفصل التمهیدي بالتعریف بالإمام مسلم و كتابه الصحیح ،أّما الفصل الأول فكان د ا رسة نظریة للخصائص الإسنادیة، أّما الفصل الأخیر فكان د ا رسة تطبیقیة للخصائص في صحیح الإمام مسلم، و قد خلصُ البحث إلى جملة من الّنتائج أهّمها:أنّ للإمام مسلم كلاما صریحا في اعتماد الخصائص داخل صحیحه، وأّنه وف ىّ بما ألزم نفسه في مقدمة كتابه، ورت بّ أغلب أحادیث أبوابه بناء على الخصائص الإسنادیة، وٕان كّررها في أبواب أخرى.This research used to deal with the impact of predicatecharacteristics in arranging a list of hadith of the chapter in Saheeh Muslim, it was establishedona preface, three chapters and conclusion , at introduction I focused on the definitions of the subject ,its significance and the reasons for my selection , then,at the introductory chapter I introduce the biography of the Imam Muslim and its book of sahih , concerning the first Chapter were discussed the characteristic΄s theory of predicate asanid , but the final chapter was practical study of the characteristics in sahih Imam Muslim, at length research has reached a number of outcomes , including that: imamMuslimhas an explicit speech in sense of adopting characteristics within his Sahih, and he fulfilled his promised which was a proclamation at the introduction of his book, and he arranged a list of hadith based on the predicate characteristics , although he repeated it in other sections
ماستر علوم الحديث
Keywords: الخصائص الإسنادية,صحيح الإمام مسلم,أحاديث; The isnad characteristics, Sahih Imam Muslim, hadiths